Comparing Patients' Experiences in Three Differentiated Service Delivery Models for HIV Treatment in South Africa. (January 2022) - Mukumbang, Ferdinand C.; Ndlovu, Sibusiso; van Wyk, Brian
Differentiated service delivery for HIV treatment seeks to enhance medication adherence while respecting the preferences of people living with HIV. Nevertheless, patients' experiences of using these differentiated service delivery models or approaches have not been qualitatively compared. Underpinned by the tenets of descriptive phenomenology, we explored and compared the experiences of patients in three differentiated service delivery models using the National Health Services' Patient Experience Framework. Data were collected from 68 purposively selected people living with HIV receiving care in facility adherence clubs, community adherence clubs, and quick pharmacy pick-up. Using the constant comparative thematic analysis approach, we compared themes identified across the different participant groups. Compared to facility adherence clubs and community adherence clubs, patients in the quick pharmacy pick-up model experienced less information sharing; communication and education; and emotional/psychological support. Patients' positive experience with a differentiated service delivery model is based on how well the model fits into their HIV disease self-management goals.